The Role of Electronic Payment Systems in Supporting the Sustainable Development Path in Iraq - Asst. Prof. Dr. Shaymaa Rasheed Mohaisen (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Electronic payment systems are increasingly recognized as critical components of modern financial systems and pathways toward sustainable development. Specific Background: In Iraq, financial inclusion remains limited, with only 23% of adults holding formal bank accounts and approximately 90% of transactions conducted in cash, reflecting structural and institutional constraints. Knowledge Gap: Despite growing interest in digital finance, there is limited integrated analysis of how electronic payment adoption aligns with sustainable development objectives within Iraq’s post-conflict and recovery context. Aims: This study examines the adoption of electronic payment systems in Iraq and evaluates their role in advancing selected Sustainable Development Goals by analyzing financial infrastructure, regulatory frameworks, and socio-economic barriers. Results: The findings reveal significant barriers including weak infrastructure, low institutional trust, socio-economic inequalities, and cultural preferences for cash, while also identifying pathways through which electronic payments can reduce transaction costs, support poverty reduction, improve gender inclusion, formalize economic activities, and strengthen governance. Novelty: The study provides a comprehensive assessment linking electronic payment systems with multiple development dimensions in a fragile economic context. Implications: The results suggest that coordinated interventions in infrastructure, regulation, and financial literacy are essential to expand digital financial services and support sustainable development trajectories in Iraq. Highlights:• Identifies structural and socio-economic barriers limiting digital financial access• Demonstrates links between digital transactions and poverty reduction pathways• Explains role of financial systems in governance transparency and inclusion Keywords: Electronic Payments, Financial Inclusion, Digital Finance, Sustainable Development, Iraq